Aedes (Stegomyia) albopictus (Skuse): a potential vector of Zika virus in Singapore. - Pei-Sze Jeslyn Wong; Mei-zhi Irene Li; Chee-Seng Chong; Lee-Ching Ng; Cheong-Huat Tan (Public Library of Science (PLoS), 2013)
Zika virus (ZIKV) is a little known arbovirus until it caused a major outbreak in the Pacific Island of Yap in 2007. Although the virus has a wide geographic distribution, most of the known vectors are sylvatic Aedes mosquitoes from Africa where the virus was first isolated. Presently, Ae. aegypti is the only known vector to transmit the virus outside the African continent, though Ae. albopictus has long been a suspected vector. Currently, Ae. albopictus has been shown capable of transmitting more than 20 arboviruses and its notoriety as an important vector came to light during the recent chikungunya pandemic. The vulnerability of Singapore to emerging infectious arboviruses has stimulated our interest to determine the competence of local Ae. albopictus to transmit ZIKV.To determine the competence of Ae. albopictus to ZIKV, we orally infected local mosquito strains to a Ugandan strain virus. Fully engorged mosquitoes were maintained in an environmental chamber set at 29°C and 80-85%RH. Twelve mosquitoes were then sampled daily from day one to seven and on day 10 and 14 post infection (pi). Zika virus titre in the midgut and salivary glands of each mosquito were determined using tissue culture infectious dose50 assay, while transmissibility of the virus was determined by detecting viral antigen in the mosquito saliva by qRT-PCR. High dissemination and transmission rate of ZIKV were observed. By day 7-pi, all mosquitoes have disseminated infection and 73% of these mosquitoes have ZIKV in their saliva. By day 10-pi, all mosquitoes were potentially infectious.The study highlighted the potential of Ae. albopictus to transmit ZIKV and the possibility that the virus could be established locally. Nonetheless, the threat of ZIKV can be mitigated by existing dengue and chikungunya control program being implemented in Singapore.